POLA PENGASUHAN ORANG TUA DENGAN PERKEMBANGAN SOSIAL ANAK RETARDASI MENTAL - Malem, Rehmaita; Fitria, Fitria; Utama, Reka Julia; Merysa, Risna (Jurnal Medikes (Media Informasi Kesehatan), 2024)
Mental retardation is a disorder in which mental development is halted or incomplete that can affect the level of intelligence or cognitive domains, including language, motor, and social skills. Children with mental retardation are less able to develop the abilities and skills of their peers. An increase in cases of mental retardation will result in a decrease in the quality of human resources. Therefore, in addition to environmental factors, the importance of completing proper nutrition will prevent neuroanatomical, neurochemical, and neurophysiological dysfunctions in humans. This study aims to analyze parenting patterns with the social development of children with mental retardation. This study used a cross-sectional design on 50 selected samples at SLB Cahaya Peureulak, East Aceh district. The results found that 62% of the sample had positive parenting patterns with 38% of children’s social development achieved and 24% of children’s social development that was not achieved. Thirty-eight percent of negative parenting patterns with social development achieved by only 12% and social development not achieved by 26%. The results of the bivariate test obtained a p-value of 0.04 (<0.05) meaning that there is a significant relationship between parenting patterns and the social development of mentally retarded children. Parental assistance for children with mental retardation dominantly influences children’s interpersonal relationships. Mentally retarded children can focus on interesting things or media with repeated learning.